Music and Motivation: A Literature-Based Review of Learning and Engagement - Piter Sembiring; Al Muqri; Lee Ji Heon (Indonesian Journal on Education (IJoEd), 2026)
This study aims to review and synthesize literature examining the relationship between music, learning motivation, and student engagement across educational settings. A literature review method was employed by analyzing twenty relevant articles on music learning. Thematic analysis was used to identify key conceptual patterns related to the role of music in enhancing motivation, supporting concentration, and influencing psychological mechanisms that foster student engagement. The findings indicate that music strengthens intrinsic motivation, regulates concentration, and promotes engagement through self-efficacy, flow experiences, and interpersonal support. Music is most effective when applied alongside responsive pedagogical strategies such as demonstration, guided practice, technological integration, and autonomy-oriented instruction. The study concludes that the intentional integration of music can improve learning quality and support the development of more student-centered instructional approaches